ANALISIS NARASI BISEKSUAL SEBAGAI BENTUK HYSTERIA TULISAN PEREMPUAN DALAM NOVEL WUTHERING HEIGHT KARYA EMILY BRONTE - Qibtiah, Mariatul (Fakultas Komunikasi, Sastra, dan Bahasa, 2012)
This research is a literature study with the novel as an object of the research. This research focuses on analyzing bisexual narration in Emily Bronte?s novel, Wuthering Heighst. The bisexual narrations themselves are shown in the ambiguities of the narration; whether it is feminine or masculine. This research aims to show the ambiguity or bisexuality narration as ?hysteria? of women's writing in one of the literary works written by Emily Bronte Wuthering Heights. The result of this research show that narration in Wuthering Heights is bisexual which is proven by the ambiguity of the narration, and that bisexual narration can be regarded as ?hysteria? of women?s writing.